Entrepreneurial Characteristics of Protected Cultivation Entrepreneurs in Pune District (Maharashtra) (Indian Journal of Extension Education, 2012)
The cultivation of crops in controlled environmental condition is known as protected cultivation. This innovative way of crop cultivation has led to increase in both quality and productivity of crops to higher level. As this technology is capital-intensive and very sophisticated, it requires certain skills and characteristics. Hence a study was conducted to analyse entrepreneurial characteristic, of protected cultivators. In this endeavour, to critically analyse the socio-economic, socio-psychological communication profile and technical skill of entrepreneurs in protected agriculture various parameters were formulated. Data were collected and analysed for understanding the correlation between these components. The study was conducted using 60 respondents in Pune district of Maharashtra as cultivation practice of cut flowers was quiet popular under protected cultivation. It was found that the majority of the entrepreneurs 56.7 per cent were of middle age and 36.7 per cent were graduate. Majority of respondents (73.3 %) showed moderate risk orientation. Large percentage of respondents had moderate to high mass media exposure. Majority of respondent had also undergone training for cultivation under protected cultivation, but still 35 per cent had not underwent any kind of special training.